Peran Organizational Citizenship Behavior Sebagai Variabel Mediasi Dalam Meningkatkan Komitmen Organisasi - Yulius, Yosandi; Marlina, Dyah Dwi; Muksin, Abdullah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The Organizational Citizenship Behavior model is interesting to study, so that it is knownthe factors that can shape Organizational Citizenship Behavior such as Organizationalculture and Work Stress to build organizational commitment. The population in this studywas used as many as 71 employees of the HR Division of the Head Office of PT. ASDPIndonesia Ferry uses a saturated sampling technique, which means that the entirepopulation is sampled. Data processing and analysis as well as hypothesis testing usingSmartPLS program version 4. The results found that the direct influence, OrganizationalCulture has a significant effect on Organizational Citizenship Behavior, Work Stress has asignificant effect on Organizational Citizenship Behavior, Organizational Culture has asignificant effect on Organizational Commitment, Work Stress and OrganizationalCitizenship Behavior has a significant effect on Organizational Commitment. WhileOrganizational Citizenship Behavior plays a full role in mediating Organizational Cultureagainst organizational commitment and Organizational Citizenship Behavior does nothave a role in mediating Work Stress against Organizational Commitment.